Alleviation of Cadmium Toxicity in Brassica juncea L. (Czern. & Coss.) by Calcium Application Involves Various Physiological and Biochemical Strategies - Ahmad, Parvaiz (PLoS One, 2015)
Calcium (Ca) plays important role in plant development and response to various environmental stresses. However, its involvement in mitigation of heavy metal stress in plants remains elusive. In this study, we examined the effect of Ca (50 mM) in controlling cadmium (Cd) uptake in mustard (Brassica juncea L.) plants exposed to toxic levels of Cd (200 mg L(−1) and 300 mg L(−1)). The Cd treatment showed substantial decrease in plant height, root length, dry weight, pigments and protein content. Application of Ca improved the growth and biomass yield of the Cd-stressed mustard seedlings. More importantly, the oil content of mustard seeds of Cd-stressed plants was also enhanced with Ca treatment. Proline was significantly increased in mustard plants under Cd stress, and exogenously sprayed Ca was found to have a positive impact on proline content in Cd-stressed plants. Different concentrations of Cd increased lipid peroxidation but the application of Ca minimized it to appreciable level in Cd-treated plants. Excessive Cd treatment enhanced the activities of antioxidant enzymes superoxide dismutase, ascorbate peroxidase and glutathione reductase, which were further enhanced by the addition of Ca. Additionally, Cd stress caused reduced uptake of essential elements and increased Cd accumulation in roots and shoots. However, application of Ca enhanced the concentration of essential elements and decreased Cd accumulation in Cd-stressed plants. Our results indicated that application of Ca enables mustard plant to withstand the deleterious effect of Cd, resulting in improved growth and seed quality of mustard plants.